2021
DOI: 10.1590/0034-7167-2020-0703
|View full text |Cite
|
Sign up to set email alerts
|

Term database for nursing practice in the context of coronavirus (COVID-19) infections

Abstract: Objective: to build a term database relevant to nursing practice in the context of COVID-19 infections. Methods: this is a methodological, documentary study, carried out from March to June 2020 at ICNP®/ Universidade Federal da Paraíba center, considered a reference for research and dissemination of ICNP® in Brazil. The findings were collected in databases and analyzed using the PorOnto tool, the consensus technique and the mapping of terms with ICNP®, version 2019/2020. Results: 1,134 relevant terms were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
6
0
2
Order By: Relevance
“…2021) and mapped to the standardised nursing languages NANDA‐I, Nursing Outcomes Classification (NOC), NIC and the 2019 version of ICNP. The results indicate that terms in ICNP represent the specific context of nursing practice for COVID‐19 patients ( de Souza et al., 2020; Santos et al., 2021).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…2021) and mapped to the standardised nursing languages NANDA‐I, Nursing Outcomes Classification (NOC), NIC and the 2019 version of ICNP. The results indicate that terms in ICNP represent the specific context of nursing practice for COVID‐19 patients ( de Souza et al., 2020; Santos et al., 2021).…”
Section: Introductionmentioning
confidence: 88%
“…Two studies using clinical data showed the value of using standardised terminologies, such as Omaha and NANDA-I, when describing nursing care of COVID-19 patients (Ardic & Turan, 2021;Asghari et al, 2021). Moreover, terms relevant to the context of COVID-19-hospitalised patients have been identified from the literature (Barros et al 2020;de Souza et al 2020;Menezes et al 2021;Santos et al, 2021), official documents (Aguña et al 2021a(Aguña et al , 2021bAraújo et al 2021) and care plans (Swanson et al 2021) and mapped to the standardised nursing languages NANDA-I, Nursing Outcomes Classification (NOC), NIC and the 2019 version of ICNP. The results indicate that terms in ICNP represent the specific context of nursing practice for COVID-19 patients ( de Souza et al, 2020;Santos et al, 2021).…”
Section: Icnp As a Reference Set In Systematized Nomenclature Of Medi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Isto posto, há a possibilidade de afirmar que os termos constantes que foram encontrados no eixo "Foco", são capazes de direcionar o enfermeiro em sua conduta de tomada de decisões na assistência à pessoa acometida por Covid-19, nos diferentes níveis de complexidade (20) .…”
Section: Discussionunclassified
“…Nesse mesmo contexto, foi identificado na literatura um estudo envolvendo o desenvolvimento de um banco de termos no contexto de infecções por Covid-19 (6) e outro referente a uma terminologia especializada de enfermagem para o cuidado à pessoa com Covid-19 (7) , no entanto, há lacunas de conhecimento relacionadas ao desenvolvimento de terminologias de enfermagem destinadas a pacientes com doenças respiratórias e Covid-19 associadas a Covid-19 é uma doença nova na humanidade, que tem causado muitas mortes precoces e inesperadas no mundo todo, para a qual a comunidade científica continua pesquisando para chegar ao tratamento específico da doença, já que, no momento os maiores avanços foram com a prevenção, notadamente com as vacinas. Assim, o desenvolvimento de estudos que possibilitem conhecer os conceitos mais prevalentes que caracterizem os fenômenos relevantes para a Enfermagem no cuidado às pessoas adultas e idosas com doenças respiratórias e Covid-19 ou que apresentaram doenças respiratórias após a Covid-19, são extremamente relevantes.…”
Section: Introductionunclassified